7 Association between low-dose aspirin use, monocyte biomarkers, matrix metalloproteinases and outcome in HFpEF. (28th September 2016) - Glezeva, N; Watson, C; Baugh, J; McDonald, K; Gilmer, J; Martin, C; Santos Martinez, M; Ledwidge, M
Abstract : Introduction: Most community heart failure patients present with preserved ejection fraction (HFpEF) associated with inflammation, monocytosis, endothelial dysfunction and platelet activation. We investigated the clinical relationship between low-dose aspirin and outcome in HFpEF and the effects of aspirin on monocyte function and cell-cell interactions in-vitro. Methods: In a retrospective analysis of HFPEF patients, we identified 150 patients taking low-dose (75 mg/day) aspirin and age/sex-matched HFPEF controls not taking aspirin over a 3 year follow-up period. From this cohort, we also studied HFPEF age/sex-matched patients (14 aspirin, 14 non-aspirin) using primary monocyte isolation, monocyte qPCR, serum matrix metalloproteinase (MMP) and inflammatory marker assays. Finally, primary monocytes were isolated from 6 healthy volunteers, analysed using flow cytometry for monocyte-platelet complexes, monocyte chemotaxis assays, and co-cultured with platelet releasate (PR, 16h) with and without aspirin. Results: Aspirin was associated with higher overall survival and lower HF hospitalisations over the 3-year follow up period (HR = 0.605, 95% confidence interval, 0.389–0.961). Serum MMP2 and sCD163 were significantly reduced in aspirin HFPEF versus matched HFPEF controls. The majority (88%) of donor monocytes were complexed with platelets. Monocyte incubation with PR caused cell activation, increased release of matrix metalloproteinas and MCP1 as well as increased monocyte invasiveness in an in-vitro transwell assay. Inflammatory cytokines (IL1alpha, IL1beta, CCL17) and gene expression of PSGL was reduced by aspirin as was monocyte invasion was reduced by 50% with aspirin treatment (p < 0.01). Conclusion: This retrospective study shows an association between the use of low-dose aspirin and better clinical outcome in HFpEF, associated with reduced sCD163 and circulating matrix metalloproteinase. These effects may be related to antiplatelet mediated modulation of monocyte function. Further work is required to evaluate antiplatelet strategies in HFpEF.